2022
DOI: 10.1093/mr/roac024
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of ultrasound as a predictor of elderly-onset rheumatoid arthritis with polymyalgia rheumatica-like onset

Abstract: Objectives Differentiation between polymyalgia rheumatica (PMR) and elderly onset rheumatoid arthritis (EORA), especially in elderly patients, is often difficult due to similarities in symptoms and serological kinetics. In this study, we aimed to analyze the predictors of EORA with PMR-like onset. Methods Seventy-two patients diagnosed with PMR, who attended our hospital for routine care and underwent musculoskeletal ultrason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…They demonstrated significantly higher grey scale and power Doppler US grades of both subacromial and subdeltoid bursitis in those with LORA vs. those with PMR [76] . The authors postulate that the differing degrees of synovial proliferation are the key pathological difference driving the contrasting US changes, with the synovitis in PMR being primarily exudative in nature vs. the predominantly proliferative synovitis observed in rheumatoid arthritis [76] . A recent retrospective study demonstrated the prognostic value of bilateral hand US in discriminating PMR from LORA, with the presence of at least one of the following increasing the probability of a diagnosis of LORA within 1 year from PMR diagnosis: rheumatoid factor positivity, grey scale synovitis in 2 of hand joints, and power Doppler positivity in 1 hand joints [77] .…”
Section: Imagingmentioning
confidence: 93%
See 2 more Smart Citations
“…They demonstrated significantly higher grey scale and power Doppler US grades of both subacromial and subdeltoid bursitis in those with LORA vs. those with PMR [76] . The authors postulate that the differing degrees of synovial proliferation are the key pathological difference driving the contrasting US changes, with the synovitis in PMR being primarily exudative in nature vs. the predominantly proliferative synovitis observed in rheumatoid arthritis [76] . A recent retrospective study demonstrated the prognostic value of bilateral hand US in discriminating PMR from LORA, with the presence of at least one of the following increasing the probability of a diagnosis of LORA within 1 year from PMR diagnosis: rheumatoid factor positivity, grey scale synovitis in 2 of hand joints, and power Doppler positivity in 1 hand joints [77] .…”
Section: Imagingmentioning
confidence: 93%
“…LORA is one of the most common mimics of PMR, and perhaps the most difficult to differentiate clinically from PMR. One study compared the semiquantitative scoring of both grey scale and power Doppler US changes in the subacromial and subdeltoid bursae of those with PMR to those with LORA [76] . They demonstrated significantly higher grey scale and power Doppler US grades of both subacromial and subdeltoid bursitis in those with LORA vs. those with PMR [76] .…”
Section: Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the presence of anti-CCP positivity in EORA and bilateral subacromial bursitis in PMR can be diagnostic aids. A recent study by Nawata et al [40] analyzed predictors of EORA with a PMR-like onset in patients initially diagnosed with PMR in 72 patients. During follow-up, 25% of these patients were subsequently diagnosed with RA.…”
Section: Clinical Features and Differential Diagnosismentioning
confidence: 99%